Single Session Effects of Prolonged Continuous Theta Burst Stimulation Targeting Two Brain Regions on Pain Perception in Patients with Painful Diabetic Neuropathy: A Preliminary Study - Bhushan Thakkar; Carrie L. Peterson; Edmund O. Acevedo (Journal of Integrative Neuroscience, 2024)
Background: Painful diabetic neuropathy (pDN) is the most common cause of neuropathic pain (NP) in the United States. Prolonged continuous theta burst stimulation (pcTBS), a form of repetitive transcranial magnetic stimulation (rTMS), is quick (1–4 minutes) and tolerable for most individuals, compared to high frequency rTMS and can modulate pain thresholds in healthy participants. However, its effects on patients with chronic pain are still unclear. The primary purpose of this preliminary study is to investigate the effects of single session pcTBS targeted at the primary motor cortex (M1) and dorsolateral prefrontal cortex (DLPFC) on a set of self-report measures of pain (SRMP) that assess the (a) sensory-discriminative; (b) affective-motivational; and (c) cognitive-evaluative aspects of pain experience. Methods: For this prospective, single-blind study, forty-two participants with pDN were randomized to receive either pcTBS targeting the M1 or the DLPFC brain regions. SRMP were completed at baseline, post pcTBS and 24h-post pcTBS. A two-way mixed model repeated measures analysis of variance (2 brain regions by 3 time points) was conducted to evaluate the effects of pcTBS stimulation at M1 and DLPFC for each subscale of each SRMP. Results: After a single session of pcTBS targeted at M1 or DLPFC in patients with pDN, statistically significant improvements from baseline to post pcTBS and baseline to 24 h-post pcTBS were observed for different SRMP subscales examining the (a) sensory-discriminative, (b) affective-motivational and (c) cognitive-evaluative components of the pain experience. At 24 h-post pcTBS, none of the participants reported any serious adverse events to the pcTBS treatment, thus demonstrating its feasibility. Conclusions: In pDN patients with NP, our study results demonstrated significant improvement in scores on self-report measures of pain (SRMP) after a single session of pcTBS targeting the M1 and DLPFC brain regions. Future studies should consider utilizing multiple sessions of pcTBS to evaluate its long-term effects on pain perception, safety and tolerability in patients with chronic pain. Clinical Trial Registration: This study was registered on the ClinicalTrials.gov website (NCT04988321).